PLEASE COMPLETE THE STORY: STORY COMPLETION TECHNIQUE IN TEACHING SPEAKING TO NON-ENGLISH MAJOR STUDENTS - Abdul Aziz Rifa’at; Nyayu Yayu Suryani (Universitas Islam Ogan Komering Ilir Kayuagung, 2018)
The aim of this study was to find out the significant difference in speaking achievement before and after the implementation of story completion technique to the 6th-semester students at STIK Siti Khadijah Palembang. The method of the study was a pre-experimental method with one group pre and posttest design approach. The population of the study was the 6th-semester students of S1 Nursing Program. The total number of the population was 90 students in the academic year 2018-2019. The sample of the study was taken by using a systematic random sampling method. The total number of the sample was 30 students. The test was given twice as a pretest and a posttest. The result of the test was analyzed by using t-test through the SPSS program. The result of the study showed that there was a significant difference in speaking achievement before and after the implementation of story completion technique to the 6th-semester students at STIK Siti Khadijah Palembang. It can be concluded that the story completion technique could be an alternative technique in teaching speaking to the students at STIK Siti Khadijah Palembang